Oil-in-water emulsion spray: A novel methodology for the enhancement of heat transfer rate in film boiling regime. (November 2018) - Pati, A.R.; Mandal, S.; Dash, A.; Barik, K.; Munshi, B.; Mohapatra, S.S.
Abstract: Minimization of Leidenfrost effect is the main controlling step for achieving high heat transfer rate in a quenching process. Hence, in the current experimental study, by using oil-in-water emulsion spray as a coolant, the Leidenfrost effect has been tried to eliminate or significantly minimize and this can be achieved by the partial vapour condensation by the low specific heat contained oil present in the evaporating emulsion droplets. Different types of emulsion are considered in the investigation for the identification of appropriate combination. The characteristic of each emulsion is identified by analyzing the images taken by confocal microscope, Leica microscope and ESEM. In addition to the above, the thermo-physical properties controlling the thermal mechanism defining from the behaviour at the interface are also measured. The quenching experiments reveal that the heat removal rate (1.44 MW/m 2 ) is the maximum for 800 ppm SDS + 30 ml kerosene emulsion among all the coolants due to the insignificant difference in properties at the interface of oil and water and the maximum condensation of produced vapour because of absorption of heat by the oil droplet present in the emulsion. However, vegetable oil-in-water emulsion depicts the minimum heat removal rate in comparison with pure water and other type of emulsions. The analysis of droplet impact mapping and boiling phenomena corroborate the findings of spray cooling.